Development of gut microbiota along with its metabolites of preschool children - Jingjing Xiong; Hongwei Hu; Chuanzhi Xu; Jianwen Yin; Mei Liu; Lizhi Zhang; Yong Duan; Yongkun Huang (BMC, 2022)
Abstract Background To reveal the changes of intestinal microbial abundance and composition, as well as the microbiota metabolic levels of bile acids and short chain fatty acids of healthy preschool children during their growth. Methods Feces of 120 healthy newborns and 150 healthy children aged 6 months to 6 years were collected. Then the composition of intestinal flora was analyzed by 16S rRNA, and the contents of bile acids and short chain fatty acids in feces were detected by LC-MS and GS methods, respectively. Results The composition and function of intestinal microflora were not stable in neonatal period but significantly improved at 6 months after birth, and gradually stabilized and tended to adult-like formation after 2-3 years old. The levels of short chain fatty acids and secondary bile acids were consistent with the development of gut microbiota. Conclusion The age of 6 months may be a critical period for the development of intestinal microflora in children.